Optimizing the SOR Method for Purchasing Decisions of Fashion Startupreneur on the Shopee Live Feature - Nuke Puji Lestari Santoso; Mardiana Mardiana; Risma Nurmala; Andzelika Birgithri; Euis Siti Nur Aisyah (Pandawan Sejahtera Indonesia, 2026)
The rapid growth of social commerce in Indonesia has opened wide opportu- nities for fashion business owners to leverage social commerce tools built into e-commerce platforms as a means of steering how consumers reach their buying choices. This study aims to examine how three core dimensions of social commerce interactivity, social presence, and informativeness affect fashion purchase decisions on the Shopee platform, using perceived value and emotional trust as mediating factors under the Stimulus Organism Response (SOR) framework. A further aim is to determine whether cognitive or affective processes play a greater role in shaping consumers’ decisions to buy fashion items online. Data were collected from Indonesian Shopee users who had previously bought fashion products from stores run by startup founders, and the data were then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings supported all of the proposed relationships. Both informativeness (β = 0.553) and interactivity (β = 0.383) showed a positive impact on perceived value, whereas social presence (β = 0.677) had a substantial positive effect on emotional trust. In turn, perceived value (β = 0.506) and emotional trust (β = 0.202) each positively influenced purchase decisions. The proposed model accounted for 74.7% of the variance in perceived value and 45.6% of the variance in purchase decisions, indicating that the cognitive route via perceived value carried more weight than the affective route via emotional trust in driving online fashion purchases. Moreover, informativeness emerged as the most impactful social commerce factor in boosting both perceived value and purchase intention.